2012
DOI: 10.1126/scisignal.2001963
|View full text |Cite
|
Sign up to set email alerts
|

Selective TRIF-Dependent Signaling by a Synthetic Toll-Like Receptor 4 Agonist

Abstract: In response to ligand binding to the Toll-like receptor 4 (TLR4) and myeloid differentiation-2 (MD-2) receptor complex, two major signaling pathways are activated that involve different adaptor proteins. One pathway depends on myeloid differentiation marker 88 (MyD88), which elicits proinflammatory responses, whereas the other depends on Toll–IL-1 receptor (TIR) domain–containing adaptor inducing interferon-β (TRIF), which elicits type I interferon production. Here, we showed that the TLR4 agonist and vaccine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
70
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 51 publications
2
70
3
Order By: Relevance
“…Although in the past, inclusion of lipid A in a vaccine was considered to be associated with an unacceptable rate of side effects, more recent work, however, suggests that the toxicity of lipid A largely depends on the species of bacteria; moreover, some chemical modifications may result in nontoxic compounds with high adjuvant activity (15,27). Studies have shown that the monophosphorylated nature of the MPL compound selectively activates the TRIF pathway of the TLR4 signaling cascade (28,29). However, it may be more beneficial for a lipid A compound to activate both TRIF and MyD88 pathways without the toxic proinflammatory side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Although in the past, inclusion of lipid A in a vaccine was considered to be associated with an unacceptable rate of side effects, more recent work, however, suggests that the toxicity of lipid A largely depends on the species of bacteria; moreover, some chemical modifications may result in nontoxic compounds with high adjuvant activity (15,27). Studies have shown that the monophosphorylated nature of the MPL compound selectively activates the TRIF pathway of the TLR4 signaling cascade (28,29). However, it may be more beneficial for a lipid A compound to activate both TRIF and MyD88 pathways without the toxic proinflammatory side effects.…”
Section: Discussionmentioning
confidence: 99%
“…This pathway, which is dependent on two adaptors, TRIF (TIR domain-containing adapter-inducing beta interferon) and TRAM (TRIF-related adaptor molecule), activates the transcription factors interferon regulatory factor 3 (IRF3) and IRF7, leading to the production of type 1 interferon (IFN) (28). Generally, while the TRIF pathway is involved in type I interferon response, the MyD88-dependent pathway triggers essentially inflammatory cytokines (29). Downstream of the MyD88 and TRIF pathways, several studies have reported the implication of MAP kinases, NF-B, and the serine/threonine kinases protein kinase C epsilon (PKC-ε), PKC-␦, PKC-, and PKC-in TLR4 signaling (30)(31)(32).…”
mentioning
confidence: 99%
“…Several studies have focused on modulation of TLR4 signaling (39,40), and TICAM-1-specific TLR4 agonists were recently generated (39,41). Although switching the molecular relationship between TLR4 and TIRAP or TICAM-2 is an attractive strategy for control of bacterial pathogenesis (39)(40)(41), it is difficult to achieve specific regulation discriminating between the MyD88-TIRAP and TICAM-1-TICAM-2 pathways without cell damage in vivo by the currently available methods.…”
Section: Discussionmentioning
confidence: 99%
“…Although switching the molecular relationship between TLR4 and TIRAP or TICAM-2 is an attractive strategy for control of bacterial pathogenesis (39)(40)(41), it is difficult to achieve specific regulation discriminating between the MyD88-TIRAP and TICAM-1-TICAM-2 pathways without cell damage in vivo by the currently available methods. TICAM-1 harbors potential to activate multifarious intracellular signaling pathways that evoke live and death events in cells with TLR3 stimulation (27,42,43).…”
Section: Discussionmentioning
confidence: 99%